The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1155/2008/369421
|View full text |Cite
|
Sign up to set email alerts
|

Active and Passive Realization of Fractance Device of Order 1/2

Abstract: Active and passive realization of Fractance device of order 1/2 is presented. The crucial point in the realization of fractance device is finding the rational approximation of its impedance function. In this paper, rational approximation is obtained by using continued fraction expansion. The rational approximation thus obtained is synthesized as a ladder network. The results obtained have shown considerable improvement over the previous techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(86 citation statements)
references
References 4 publications
1
85
0
Order By: Relevance
“…It was reported that such FOD can be represented using continued fraction expansions (CFE) [27] expressed by rational functions of the Laplace independent variable s -resulting in an infinite RC ladder network (see Fig. 1), [7,11]. However, by limiting the frequency range of application for the CPE, one can design a module composed of a finite number of components such as a finite ladder by truncating the CFE [22] that can approximately work as a CPE for the specific range of interest, and eventually become a practically-acceptable FOD [20,21] for various applications.…”
Section: Theory and Realization Of Fractional-order Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that such FOD can be represented using continued fraction expansions (CFE) [27] expressed by rational functions of the Laplace independent variable s -resulting in an infinite RC ladder network (see Fig. 1), [7,11]. However, by limiting the frequency range of application for the CPE, one can design a module composed of a finite number of components such as a finite ladder by truncating the CFE [22] that can approximately work as a CPE for the specific range of interest, and eventually become a practically-acceptable FOD [20,21] for various applications.…”
Section: Theory and Realization Of Fractional-order Elementsmentioning
confidence: 99%
“…The use of RC ladders [8,30] have been exercised since the mid-20th century for realizing fractional-order elements [1,7,10,11], but the approximation results were disappointing-having only a very limited bandwidth with a high number of components. An improved version of the RC ladder was introduced in [28] and has shown to be superior over its predecessors having only a small amount of components needed to perform as a CPE at a better bandwidth.…”
Section: Theory and Realization Of Fractional-order Elementsmentioning
confidence: 99%
“…These methods present a large array of approximations with varying order and accuracy, with the accuracy and approximated frequency band increasing as the order of the approximation increases. Here, a CFE method [24] was selected to model the fractional capacitors for PSPICE simulations. Collecting eight terms of the CFE yields a 4 th order approximation of the fractional capacitor that can be physically realized using the RC ladder network in Fig.…”
Section: Pspice Simulationsmentioning
confidence: 99%
“…The original approach, developed by Oustaloup [26,27], is based on approximation of fractional systems in frequency domain. This approach is widely used, e.g., [11,22,25,32] and many others. However, this method has some flaws which cannot be neglected-when discretized, it does not guarantee stability of the system (the poles of discrete system are outside unit circle) (see, e.g., [30]).…”
Section: Introductionmentioning
confidence: 99%